Optimization of a tunable process for rapid production of calcium phosphate microparticles using a droplet-based microfluidic platform - Alaoui Selsouli, Y.; Rho, H. S.; Eischen-Loges, M.; Galván-Chacón, V. P.; Stähli, C.; Viecelli, Y.; Döbelin, N.; Bohner, M.; Tahmasebi Birgani, Z.; Habibović, P. (Frontiers in Bioengineering and Biotechnology, 2024)
Calcium phosphate (CaP) biomaterials are amongst the most widely used synthetic bone graft substitutes, owing to their chemical similarities to the mineral part of bone matrix and off-the-shelf availability. However, their ability to regenerate bone in critical-sized bone defects has remained inferior to the gold standard autologous bone. Hence, there is a need for methods that can be employed to efficiently produce CaPs with different properties, enabling the screening and consequent fine-tuning of the properties of CaPs towards effective bone regeneration. To this end, we propose the use of droplet microfluidics for rapid production of a variety of CaP microparticles. Particularly, this study aims to optimize the steps of a droplet microfluidic-based production process, including droplet generation, in-droplet CaP synthesis, purification and sintering, in order to obtain a library of CaP microparticles with fine-tuned properties. The results showed that size-controlled, monodisperse water-in-oil microdroplets containing calcium- and phosphate-rich solutions can be produced using a flow-focusing droplet-generator microfluidic chip. We optimized synthesis protocols based on in-droplet mineralization to obtain a range of CaP microparticles without and with inorganic additives. This was achieved by adjusting synthesis parameters, such as precursor concentration, pH value, and aging time, and applying heat treatment. In addition, our results indicated that the synthesis and fabrication parameters of CaPs in this method can alter the microstructure and the degradation behavior of CaPs. Overall, the results highlight the potential of the droplet microfluidic platform for engineering CaP microparticle biomaterials with fine-tuned properties.